(untitled) (Veterinary Science, 2017)
In countries that have managed to eradicate bovine tuberculosis, has been shown to interfere with certain MNT tuberculosis diagnosis, when applied to the intradermal purified protein derivative Mycobacterium bovis PPD. It has also been established that some species can invade and replicate MNT inside Acanthamoeba parasites such as Dictyostelium discoideum, these protozoa may act as reservoirs of MNT mammals parasitized. Exist in mammals in the natural environment of lakes, sewage, soil, environmental dust,etc.,and manmade artificial enviroments such as drinking water, aquariums, plactonica and biofilms. The objectives of the proyect were to develop the sensitines (PPD) from the isolates of NTM isolated from soils of the province of La Pampa and check possible cross-reaction with PPD bovine.Two sensitines series of Mycobacterium fortuitum corresponding to and another Mycobacterium phlei, with protein concentration of 1.5 mg/mL. Guinea pigs were sensitized with Mycobacterum phlei, Mycobacterium fortuitum and Mycobacterium bovis power with sterile vaseline and pumice. After 120 days tests potency were carried out on the flanks of guinea pigs. The relative activity in guinea pigs sensitized with Mycobacterium bovis was of 2.18% with M.phlei and of 0.4% for the PPD Mycobacterium fortuitum ,wich shows that the environmental mycobacteria had no relevant actions in guinea pigs tuberculin intradermal reaction